2SPD-039 Make or buy: pharmacoeconomic evaluation of gargle solutions used for SARS-CoV-2 sample collection. (14th March 2021) - Lindner, N; Haider, D
Abstract : Background and importance: The SARS-CoV-2 pandemic has become a major public health issue around the world. Samples for viral detection are generally obtained through nasopharyngeal or oropharyngeal swabs. Several studies have investigated gargling as an alternative method for sample collection. This offers various advantages for patients, particularly in the paediatric setting, as well as for healthcare personnel. Different media for gargling exist, which led to a pharmacoeconomic comparison of the available products. Aim and objectives: The aim of this study was to compare the cost of products, which can be used as gargling solutions for SARS-CoV-2 sample collection. Material and methods: Phosphate buffered saline (PBS) in tubes was requested by the laboratory department as a gargling solution for specimen collection in a clinical trial in children. Since no pharmaceutically approved PBS products are available, the pharmacy department could either compound the solution or commission a contract manufacturer. Physiological saline, available as a pharmaceutically approved product, could function as an alternative to PBS. The prices of all three products and potential cost reductions were directly compared. Costs for pharmacy production were calculated, estimating an average production and packaging time of 26 hours for a batch of 1000 tubes, while running costs for available infrastructure were neglected. Results: Conclusion and relevance: While the contract manufacturer delivers GMP certified products at high cost, non-certified pharmacy productions cannot reach these quality standards. Product changes, in this case from PBS to the equally validated physiological saline, act as a valuable measure aiming at cost reductions. Pharmacy departments play an important part in evaluating availability, practicability and particularly cost effectiveness of desired products and should thus be included in the decision making process. References and/or acknowledgements: Conflict of interest: No conflict of interest